The Potential Role of Nanotechnology in Therapeutic Approaches for Triple Negative Breast Cancer - Andras G. Lacko; Rebecca Johnson; Nirupama Sabnis; Walter J. McConathy (MDPI AG, 2013)
Triple Negative Breast Cancer, TNBC, a highly aggressive and metastatic type of breast cancer, is characterized by loss of expression of the estrogen receptor (ER), progesterone receptor (PR), and a lack of overexpression of the human epidermal growth factor receptor 2 (HER2). It is a heterogeneous group of tumors with diverse histology, molecular uniqueness and response to treatment. Unfortunately, TNBC patients do not benefit from current anti-HER2 or hormone positive targeted breast cancer treatments; consequently, these patients rely primarily on chemotherapy. However, the 5-year survival rate for woman with metastatic TNBC is less than 30%. As a result of ineffective treatments, TNBC tumors often progress to metastatic lesions in the brain and lung. Brain metastases of invasive breast cancer are associated with 1 and 2 year survival rate of 20% and <2% respectively. Because the only current systemic treatment for TNBC is chemotherapy, alternative targeted therapies are urgently needed to improve the prognosis for TNBC patients. This review is focused on opportunities for developing new approaches for filling the current void in an effective treatment for TNBC patients.